Jurnal Analisis Faktor Yang Mempengaruhi Minat Belajar Siswa Kelas XI IPS Terhadap Mata Pelajaran Geografi di SMA Santun Untan Pontianak: Minat Belajar - ntn, riska; Prihadi, Adhitya; Paiman (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2024)
This research aims to determine student’s interest in learning about Geography subject. This researchuses a qualitavie research method in the form of qualitative descriptive. The data sources in this research areGeography teachers and class XI IPS students. Data collection techniques use direct observation, directcommunication, and documentary studies. The data collection tools used were observation guides, interview guides,and documentation. The data analysis techniques used are data collection, data reduction, data presentation, anddrawing conclusion. The result of the research that has been carried out reveal that studen’s interest in learning isrelatively good, this can be seen when students listen well when learning, prepare to start learning by taking out worksheets, and often ask the teacher about material that is unclear.